Case Report: Reproductive evaluation of a Murgese stallion with obstructive azoospermia, accumulation of hyaline material in the ampullae ducts, and corpora amylacea in vesicular glands - Bucci, Roberta; Parrillo, Salvatore; Probo, Monica; Varasano, Vincenzo; Romano, Anastasia; Carluccio, Augusto (Frontiers in Veterinary Science, 2025)
This report aims to present a case of obstructive azoospermia in a stud stallion diagnosed with an alkaline phosphatase (SPAP) assessment. A 20-year-old Murgese stallion is referred for acquired azoospermia. History is negative for reproductive disorders, and clinical examinations and ultrasonography of internal and external genitalia do not reveal significant alterations. Semen collection highlights the absence of spermatozoa in the ejaculate and the urinalysis is negative for spermatozoa. SPAP assay is performed on seminal plasma, with a value of 30 IU/L, compatible with obstructive azoospermia. A biopsy is performed, detecting the presence of complete germ lines in both testes. A resolution is attempted endoscopically, gently insufflating ampullae, with negative results, so the stallion is excluded from breeding. Time afterwards, the stallion dies of natural causes, and necropsy and histopathological analyses are performed. Corpora amylacea are highlighted in both seminal vesicles; the right and left ampullae show ectasic lumen, with the diffuse presence of hyaline material. Ampullae obstruction is an uncommon pathology, which can affect stallions and jacks, generally caused by the accumulation of spermatozoa, but, unfortunately, this case was unresponsive to attempted treatments. Interestingly, to the authors’ knowledge, this is the first report of corpora amylacea in equine stallion sexual glands.